PEDAGOGICAL POSSIBILITIES OF THE WORK “THE WHITE SHIP” IN DEVELOPING EMPATHY IN STUDENTS - Shoyimova Shoira Sanakulovna (International Journal of Literature and Language Studies, 2026)
The article analyzes the pedagogical potential of fiction, in particular Chingiz Aitmatov's story "The White Ship", in developing students' reflexive-empathic competence based on empathy and its reflexive processing. The system of images of the work is studied from the point of view of empathy reading of the legend of the boy, the old man Momin, Orozkul and the mother deer, and a system of tasks is proposed based on the text, which develops students' emotional-intellectual and reflexive skills. The results of the analysis show that empathic and reflexive understanding of the fate of the heroes of the story serves to develop empathy, tolerance and critical thinking in students.